STRATEGI SATUAN PENDIDIKAN ANAK USIA DINI (PAUD) DALAM MENCEGAH BULLYING DI RA ANNIDHAMIYAH BINDANG PASEAN PAMEKASAN - Mudrikatul Amaniyah; Danang Prastyo (JCE (Journal of Childhood Education), 2025)
This study aims to identify and analyze the strategies implemented by the Early Childhood Education (ECE) Unit at RA Annidhamiyah Bindang Pasean Pamekasan in preventing bullying among children. The research method used is descriptive qualitative with observation, interview, and documentation approaches. The results showed that the strategies implemented by RA Annidhamiyah involved curriculum, psychological, social, and teacher and parent training approaches. The curriculum approach includes character education, habituation of mutual respect, and introduction of empathy values through daily activities. The psychological approach includes early identification of children who are potential perpetrators or victims of bullying, as well as individual and group counseling to improve social and emotional skills. The social approach emphasizes the establishment of an inclusive and supportive school culture and involving parents in supporting children's character building. However, challenges include a lack of cooperation between parents and institutions as well as social and cultural views that are less supportive of bullying prevention. Although there is a need to raise awareness and encourage community and parent involvement in bullying prevention initiatives, the tactics used at RA Annidhamiyah have generally had excellent outcomes in building a safe and supportive learning environment for children's growth. With this research, it can provide information related to strategies that can be implemented in preventing bullying for Education Units at the Early Childhood Education (PAUD) level in Indonesia.